RESEARCH ON MECHANICAL CHARACTERISTICS OF NEW MOBILE ROLLER BRACKET CONVEYOR - ZHANG DongSheng; HE JinLong; NI Xue (Jixie qiangdu)
In this paper,a new type of moving roller bracket conveyor is taken as the research object. The simulation of Adams virtual prototype is carried out on the mechanical model of the roller bracket to obtain the contact force of the wheel and rail under two working conditions. On the basis of dynamic simulation,static simulation analysis of the conveyor under different working conditions was carried out by using finite element software Ansys to obtain the maximum stress and strain,and the safety factor of each component was calculated to verify the structural rationality. The dynamic response analysis of the reversing frame and the separation frame is carried out by using the New mark integration method in ANSYS workbench,and the displacement and acceleration transient values are obtained. The results show that after the load is applied,the contact force of the conveyor wheel rail will change,but the weak position of the roller carriage conveyor will not be moved,and the abnormal variation in the Z-axis direction indicates the uncontrollability of the lateral load. Provide a theoretical basis for the structural improvementof the moving roller carriage conveyor.